Inflammation, oxidative stress and platelet activation in aspirin-treated critical limb ischaemia: Beneficial effects of iloprost - Lessiani, Gianfranco; Vazzana, Natale; Cuccurullo, Chiara; Di Michele, Dario; Laurora, Giuseppe; Sgrò, Giuseppe; Di Ruscio, Paolo; Simeone, Emilio; Di Iorio, Pierangelo; Lattanzio, Stefano; Liani, Rossella; Ferrante, Elisabetta; Davì, Giovanni (Thrombosis and Haemostasis, 2011)
Platelets critically contribute to atherothrombosis and worsening ischaemia in patients with peripheral arterial disease (PAD), eventually leading to critical limb ischaemia (CLI). Furthermore, persistent platelet activation despite antiplatelet therapy has been reported in this setting. The prostacyclin analogue iloprost is currently recommended in CLI patients for its effects in relieving symptoms by promoting local perfusion. In this study, we investigated the effects of iloprost infusion on urinary 11-dehydro-TXB2 and 8-iso-PGF2α excretion rate, as in vivoindexes of thromboxane-dependent platelet activation and lipid peroxidation, respectively, and on platelet-derived proinflammatory sCD40L and nitric oxide bioavailability in 44 patients with CLI while on chronic treatment with low-dose aspirin. Daily iloprost infusion for one-week significantly decreased urinary 11-dehydro-TXB2 [499 (277 – 807) vs. 380 (189 – 560) pg/mg creatinine, p < 0.0001] and 8-iso-PGF2α [533 (316 – 842) vs. 334 (196 – 540) pg/mg creatinine, p < 0.0001] as well as plasma sCD40L [1540 (1005 – 3015) vs. 948 (845 – 2030) pg/ml, p < 0.0001]. Furthermore, a significant increase in plasma nitrate plus nitrite levels has been observed [26.8 (18.8 – 35.9) vs. 43.7 (33.0 – 75.5) μM, p < 0.0001]. A significant direct correlation was also found between urinary 8-iso-PGF2α and 11-dehydro-TXB2 before and after iloprost treatment (Rho = 0.695, p < 0.0001). In conclusion, we report that a short-term course of iloprost is able to significantly reduce residual thromboxane biosynthesis, oxidative stress, endothelial dysfunction and platelet-derived inflammation in low-dose aspirin treated patients with CLI.
Keywords: Platelet; inflammation; iloprost; oxidative stress; endothelial dysfunction; critical limb ischaemia